Thyroid cancer in children: A multicenter international study highlighting clinical features and surgical outcomes of primary and secondary tumors - Martucci, Cristina; Crocoli, Alessandro; De Pasquale, Maria Debora; Spinelli, Claudio; Strambi, Silvia; Brazzarola, Paolo; Morelli, Eleonora; Cassiani, Jessica; Mancera, Juliana; Luengas, Juan Pablo; Lobos, Pablo; Liberto, Daniel; et al. (Frontiers in Pediatrics, 2022)
Background: Thyroid gland malignancies are rare in pediatric patients (0.7% of tumors); only 1.8% are observed in patients aged < 20 years, with a higher prevalence recorded in women and adolescents. Risk factors include genetic syndromes, MEN disorders, autoimmune diseases, and exposure to ionizing radiation. Radiotherapy is also associated with an increased risk of secondary thyroid cancer. The present study describes the clinical features and surgical outcomes of primary and secondary thyroid tumors in pediatric patients. Methods: Institutional data were collected from eight international surgical oncology centers for pediatric patients with thyroid cancer between 2000 and – 2020. Statistical analyses were performed using the GraphPad Prism software. Results: Of 255 total cases of thyroid cancer, only 13 (5.1%) were secondary tumors. Primary thyroid malignancies were more likely to be multifocal in origin (odds ratio [OR] 1.993, 95% confidence interval [CI] 0.7466-5.132, p 0.2323), have bilateral glandular location (OR 2.847, 95% CI 0.6835-12.68, p 0.2648), and be metastatic at first diagnosis (OR 1.259, 95% CI 0.3267-5.696, p>0.999). Secondary tumors showed a higher incidence of disease relapse (OR 1.556, 95% CI 0.4579-5.57, p 0.4525) and surgical complications (OR 2.042, 95% CI 0.7917-5.221, p 0.1614), including hypoparathyroidism and recurrent laryngeal nerve injury. The overall survival (OS) was 99% at one year and 97% after ten years. No EFS differences were evident between the primary and secondary tumors (chi-square 0.7307, p 0.39026). Conclusions: This multicenter study demonstrated excellent survival in pediatric thyroid malignancies. Secondary tumors exhibited greater disease relapse (15.8% vs. 10.5%) and a higher incidence of surgical complications (36.8% vs. 22.2%).